Procedings of the British Machine Vision Conference 1996 1996
DOI: 10.5244/c.10.70
|View full text |Cite
|
Sign up to set email alerts
|

Finding Orientated Line Patterns in Digital Mammographic Images

Abstract: In mammography the presence of subtle abnormalities such as stellate patterns and architectual distortions indicates possible malignancy. Radiologists do not always detect these abnormalities in screening mammograms; this has led to interest in computer-aided mammographic interpretation where the radiologist is presented with computer-generated 'prompts' for abnormalities. A first step in this process is the detection of the "orientation", "scale" and "strength" of linear structures in the mammograms. We discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Zwiggelaar et al [89] investigated the performance of different methods for the detection and classification of CLS in mammograms, including: a line operator [90], orientated bins [91], steerable filters [92], and ridge detectors [93]. It was observed that the best method for CLS detection (line operator) yielded an area under the ROC curve of A z ¼ 0:94.…”
Section: Article In Pressmentioning
confidence: 98%
“…Zwiggelaar et al [89] investigated the performance of different methods for the detection and classification of CLS in mammograms, including: a line operator [90], orientated bins [91], steerable filters [92], and ridge detectors [93]. It was observed that the best method for CLS detection (line operator) yielded an area under the ROC curve of A z ¼ 0:94.…”
Section: Article In Pressmentioning
confidence: 98%
“…Multiscale techniques are thus often employed in vessel segmentation in order to overcome this problem. A relatively straightforward multiscale approach is provided by the multiscale line operator (MSLO) [24][25][26][27][28]. This method has been used with great success in detecting linear structures in mammograms [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…GAVAGHAN et al range of spatial scales in mammograms. More recent work (Zwiggelaar et al, 1996) attempts to detect CLS using a set of "modal variations" determined by principal components analysis on a training set of idealised cases of CLS. Current work aims to apply recently developed techniques for feature detection, based largely on the observed phase congruency of features.…”
Section: Detecting and Removing Clsmentioning
confidence: 99%